2021
DOI: 10.1101/2021.06.28.21258847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Side Effects and Perceptions Following Sinopharm COVID-19 Vaccination

Abstract: Objectives Vaccines are one of the best interventions developed for eradicating COVID-19 the rapid creation of vaccinations was increased the risk of vaccine safety problems. The aim of this study to provide evidence on Sinopharm COVID-19 vaccine side effects. Methods A cross-sectional survey study was conducted between January and April 2021 to collect data on the effects of COVID-19 vaccine among individuals in the UAE. Demographic data chronic conditions side effects of the 1st and 2nd dose toward the vacc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 22 publications
8
38
2
1
Order By: Relevance
“…Another study conducted in USA also showed similar results [11]. Similar results were shown by another study conducted in UAE [14]. A study done in Poland showed that 78% participants experienced soreness at site of injection which was comparable to our study [15].…”
Section: Resultssupporting
confidence: 91%
“…Another study conducted in USA also showed similar results [11]. Similar results were shown by another study conducted in UAE [14]. A study done in Poland showed that 78% participants experienced soreness at site of injection which was comparable to our study [15].…”
Section: Resultssupporting
confidence: 91%
“…Vaccination is regarded as the best preventive intervention against the COVID‐19 infection and is believed to save millions of lives each year 2 . Several brands of COVID‐19 vaccines have been developed, including Sinopharm 4 that works based on the virus inactivating technology and promotes immunity by introducing inactivated SARS‐CoV‐2 viruses into the body 2 …”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus infection disease 2019 (COVID‐19), the recent pandemic ravaging the world, is a serious health threat to mankind. Current research on COVID‐19 vaccines shows that most of their known side effects are mild and self‐limiting and do not require any specific treatment 1,2 . However, some rare and partially recognized side effects of these vaccines may create serious life‐threatening conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Notably, severe allergic reaction to vaccines is rare, 2 and the female gender was found to be consistently associated with an increased risk of side effects following receiving different types of COVID-19 vaccines. 3,4 The safety of three types of COVID-19 vaccines, including Pfizer, AstraZeneca, and Sinopharm, was recently studied. Accordingly, the investigators found that the systemic events were more common with AstraZeneca and Pfizer vaccines, and the symptoms reported in this regard were fatigue, body pain, headache, muscle pain, fever, and gastrointestinal side effects.…”
Section: F I G U R E 1 (A-g) a 63-year-old Woman With Bullae On Upper...mentioning
confidence: 99%